CRISPR-Fortschritte: Schnitt für Schnitt zu neuen Möglichkeiten - Pakari, Kaisa; Wittbrodt, Joachim; Thumberger, Thomas (Biospektrum, 2023)
CRISPR/Cas9 systems and recently established base editors are essential tools for precise, targeted genome editing for translational and basic research applications. Here we present small, easily combined improvements to reach editing versatility and enhanced efficiency. This is achieved by improved nuclear localization of Cas9, protected DNA sequences for homology directed repair and a combinatorial use of base editors to reach initially inaccessible target sites.